2018
DOI: 10.3390/su10124772
|View full text |Cite
|
Sign up to set email alerts
|

Delay Factors in Reconstruction Projects: A Case Study of Mataf Expansion Project

Abstract: Delays in construction projects are a common phenomenon throughout the industry. This problem has many negative impacts on the time, cost, and sustainability of the projects. Many studies were conducted to identify the main causes of this delay in new construction projects in different regions but very few studies have focused on finding an explanation for the causes of delay in major reconstruction projects that have great religious and cultural sustainability. This paper examines the factors that contributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Unique factors (with the frequency of three or less) are: "'Slow decision making process by owner" in Norway [90], UAE [84], and Oman [98]; "Changes in material types and specifications during construction" in Saudi Arabia [102], Turkey [117], and Zambia [113]; "Change/selection of subcontractors in the project" in India [79], Saudi Arabia [112], and Vietnam [105]; "Mobilization delay" in India [127], Malaysia [109], and Malawi [81]; "Site constraints (site blockage, impact of other's land)" in Bangladesh [87], Cambodia [103], and countries with high geopolitical risks [104]; "Impact of subsurface (underground) conditions" in Libya [91], Cambodia [103], and Egypt [123]; "Conflict between parties' in Iran [101], Turkey [70], and Egypt [107]; "Errors in construction" in Iran [93], Zambia [113], and Denmark [89]; "Fluctuation in price of materials" in Saudi Arabia [102] and Ghana [100]; "Conflict between labours" in Saudi Arabia [88] and Zambia [113]; "Labour strikes" in countries with high geopolitical risks [104] and Zambia [113]; "Using inappropriate construction methods" in India [92] and Iran [110]; "Insufficient/inaccurate document preparation" in Turkey [70] and Iran [110]; "Inaccurate first drafts/plan" in Iran [110] and Taiwan [132]; "Delay/weak interaction due to vendor" in India [127] and Oman…”
Section: Key Factors Identified In the Delay Literaturementioning
confidence: 99%
“…Unique factors (with the frequency of three or less) are: "'Slow decision making process by owner" in Norway [90], UAE [84], and Oman [98]; "Changes in material types and specifications during construction" in Saudi Arabia [102], Turkey [117], and Zambia [113]; "Change/selection of subcontractors in the project" in India [79], Saudi Arabia [112], and Vietnam [105]; "Mobilization delay" in India [127], Malaysia [109], and Malawi [81]; "Site constraints (site blockage, impact of other's land)" in Bangladesh [87], Cambodia [103], and countries with high geopolitical risks [104]; "Impact of subsurface (underground) conditions" in Libya [91], Cambodia [103], and Egypt [123]; "Conflict between parties' in Iran [101], Turkey [70], and Egypt [107]; "Errors in construction" in Iran [93], Zambia [113], and Denmark [89]; "Fluctuation in price of materials" in Saudi Arabia [102] and Ghana [100]; "Conflict between labours" in Saudi Arabia [88] and Zambia [113]; "Labour strikes" in countries with high geopolitical risks [104] and Zambia [113]; "Using inappropriate construction methods" in India [92] and Iran [110]; "Insufficient/inaccurate document preparation" in Turkey [70] and Iran [110]; "Inaccurate first drafts/plan" in Iran [110] and Taiwan [132]; "Delay/weak interaction due to vendor" in India [127] and Oman…”
Section: Key Factors Identified In the Delay Literaturementioning
confidence: 99%
“…Among them, owner-related causes were the owner's slow decisions, shop drawings and samples' slow preparation and approval, the owner's change orders during construction, owner's financial problems for the project, and owner's delay in contractors' progress payment. As owner-related causes of delay, Khatib et al [24] suggested their financial problems and difficulties, change orders, delays and shortages of materials, poor site management and supervision, poor communication and coordination among construction parties, lowest bid awards, slow decisions, the contract type, delays in performing inspections and tests, and lack of clarity of the project's scope. Alsuliman [18] used a questionnaire to investigate the causes of delay according to stages of a public construction project.…”
Section: Owner-related Causes Of Delaymentioning
confidence: 99%
“…Aziz and Abdel-Hakam's [17] study also identified contractor-related factors, such as their poor site management and supervision, construction methods, ineffective project planning, and scheduling, financing during construction, and inadequate experience that caused errors as highly frequent causes of delay. Khatib et al [24] suggested improper planning and scheduling, subcontractor's incompetence, contractor's lack of experience, discrepancies between drawings and specifications, construction mistakes and defective work, inaccurate estimates, inadequate tools and equipment, and price escalation.…”
Section: Contractor-related Causes Of Delaymentioning
confidence: 99%
See 2 more Smart Citations